PENINGKATAN NILAI JUAL KURSI KAYU DAN VARIASI DRUM DI KARANG TARUNA - Hadita, Hadita; Sari, Rycha Kuwara; Sulistyowati, Ari (Economic Faculty, Attahiriyah Islamic University, 2019)
This study aims to test and determine the increasing value of wooden chair seats and drum variations based on business capital, production process, and product marketing. The subject of this study is the RW community, 18 Harapan Jaya Sub-district - North Bekasi. The results of this study are the lack of capital so that small businesses Karang Taruna is less able to compete in the market so that access in marketing is hampered and Marketing System is only limited from word to mouth and relying on social media from some members of youth caustic so minimal prospects. From some of these things have an effect on the selling value of the products of youth cadets that are far from the desired expectations. Keywords: selling point, business capital, production, process, product marketing